How intra- and interfirm agglomeration affect new-unit geographic distance decisions of multiunit firms - Woo, Hyun-Soo; Cannella, Albert; Mesquita, Luiz (Strategic Management Journal, 2019)
[Research Summary:Prior agglomeration research takes a competitive-level view, where any incumbent is considered as a rival by a new entrant in the same geographic market. Our study suggests an alternative corporate-level view, where entry by multiunit firms must consider sister units as well as rivals in the market. Theorizing about a sharing mechanism between sister units distinct from a spillover mechanism between rivals, we expect that multiunit firms locate new units nearer sister vis-à-vis rival units and that the size, quality, and organizational form of a new unit moderate these associations. Finally, we predict that multiunit firms establish new units distant from same-brand and same-market-segment sister units. We find robust empirical support from the geographic distance decisions of 10 multiunit hotel firms in 20 U.S. cities. Managerial Summary:Where should multiunit firms (e.g., fast-food chains, hotels) locate new business units relative to others? Current competitive-level-strategy perspective argues new units should locate “far-from-others” if they have superior capabilities (to avoid being imitated) and “near-others” if inferior ones (to better imitate others). We instead examine this phenomenon from a corporate-level-strategy perspective, regarding locally available synergies sister units can garner to better compete. We argue that new units locate nearer sister (i.e., business-units of same-parent firms) than rival units; that this effect is stronger if new units are larger, have better quality, and are company-operated rather than franchised; and that this base effect is weaker when sisters belong to same- rather than different-brand companies of the same parent-firm. We provide supporting empirical evidence from the hotel industry.]